Design strong anomalous Hall effect via spin canting in antiferromagnetic nodal line materials - Le, Congcong; Felser, Claudia; Sun, Yan (Physical Review B, 2021)
The interplay between magnetism and the topological electronic structure provides a large freedom for designing strong anomalous Hall effect (AHE) materials. A nodal line from band inversion is a typical band structure for generating strong AHE. On the other band, in most collinear antiferromagnets (AFMs), the integral of the Berry curvatures on the Brillouin zone is forced to zero by the joint symmetry, where and are the time reversal and a space group operation, respectively. Even with inverted band structures, such AFM cannot have an AHE. Therefore, the AFM nodal line band structures constructed by spin degenerated bands do not receive much attention in AHE materials. In this work, we illustrate that such a band structure provides a promising starting point for generating strong local and net Berry curvature and, hence, strong intrinsic AHE. In specific AFM compounds of ( and Yb) with an inverted band structure, we observed a strong AHE induced by a weak spin canting from temperature or doping. The anomalous Hall conductivity continues to grow with the canting angle owing to the nodal line in the band structure. Since such spin canting can be adjusted experimentally via doping, it provides another effective strategy to generate and manipulate a strong AHE.
CRIS-Team Scopus Importer:2022-04-14